Quality Assurance Strategy in Maintaining School Integrity and Community Trust to Strengthen the Foundations of Education Quality - Nasikhah, Wulan Roudhotul; Sultoni, Sultoni; Rochmawati, Rochmawati (Faculty of Educational Sciences, Universitas Negeri Yogyakarta, 2024)
This research aims to determine internal and external quality assurance strategies in maintaining school integrity and community trust in order to strengthen the foundation of educational quality. This research uses a qualitative approach with a case study type of research. Data collection techniques use interviews, observation and document study. The research results show that: (1) the school emphasizes character building and improving internal quality as a strategy to maintain its integrity; (2) transparent communication and promotion of academic achievements through social media are used to build public trust; (3) the strategy used by schools to achieve an A predicate in the accreditation process is to implement team work; (4) the school takes steps to prepare for accreditation which include understanding standards, planning, team formation, submitting applications, simulations, visitations, internal evaluations, and follow-up; and (5) the school received the highest assessment in the accreditation results for the school management component and the quality of graduates. Based on the research results, it can be concluded that the internal and external quality assurance strategies implemented by schools are very important to maintain school integrity and community trust in strengthening the foundations of educational quality. Internal quality assurance has a more dominant role in maintaining school integrity and strengthening the foundation of educational quality.